2020
DOI: 10.3390/medicina56050247
|View full text |Cite
|
Sign up to set email alerts
|

Actual Nutrition and Dietary Supplementation in Lithuanian Elite Athletes

Abstract: Background and objectives: Health is partly determined by the state of one’s nutrition; it stimulates the body’s functional and metabolic adaptations to physical strain and helps one prevent sports injuries and get in shape in terms of body composition. This study aims to investigate the actual nutrition and dietary supplements taken by elite Lithuanian athletes and to identify the relationship between the dietary intake, dietary supplementation and body composition of elite athletes. Materials and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
11
2
Order By: Relevance
“…To our knowledge, this is the first research study to examine the prevalence of supplementation in recreational endurance athletes whilst also considering the two different sporting disciplines of cycling and triathlon. The proportion of participants that reported often taking supplements in our study is much lower than that reported in other studies with professional athletes 45 , 46 . The majority of participants who took supplements opted to take protein, multivitamins, minerals and omega-3.…”
Section: Discussioncontrasting
confidence: 93%
“…To our knowledge, this is the first research study to examine the prevalence of supplementation in recreational endurance athletes whilst also considering the two different sporting disciplines of cycling and triathlon. The proportion of participants that reported often taking supplements in our study is much lower than that reported in other studies with professional athletes 45 , 46 . The majority of participants who took supplements opted to take protein, multivitamins, minerals and omega-3.…”
Section: Discussioncontrasting
confidence: 93%
“…To our knowledge, this is the rst research study to examine the prevalence of supplementation in recreational endurance athletes whilst also considering the two different sporting disciplines of cycling and triathlon. The proportion of participants that reported often taking supplements in our study is much lower than that reported in other studies with professional athletes [35][36] . The majority of participants who took supplements, opted to take protein, multivitamins, minerals and omega-3.…”
Section: Discussioncontrasting
confidence: 91%
“…For instance, evidence indicates that females in track and field [ 48 ] and males in strength sports [ 68 ] use more supplements compared to their counterparts of the opposite sex. Additionally, evidence shows that despite no overall sex-based difference in the amount of supplement intake [ 62 ], male athletes were more likely to consume protein and ergogenic supplements associated with maintaining and improving muscle mass/strength, and female athletes were most likely to consume micronutrient supplements, which are typically considered health-related supplements [ 62 , 63 , 65 , 66 , 69 ]. This general sex-based difference in the type of supplement intake could be associated with either the greater training volume of male than female runners [ 67 ] or the different sex-based intrinsic causes to use dietary supplements; males reported the gain of muscle mass and strength/power as a higher priority than health or meeting dietary guidelines and females mentioned health as their first priority for consuming dietary supplements [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the type of supplement, the present results showed that vitamin supplements had the most usage prevalence in male and female runners alike. Despite consistent data indicating the higher prevalence of multivitamins among athletes [ 72 , 73 ], there is some contradictory evidence demonstrating proteins [ 62 ] or carbohydrates [ 69 ] are the supplements most taken by athletes, especially male athletes [ 69 ]. While this difference could potentially be contributing to the higher number of vegan/vegetarian runners in the present study, different nutritional requirements of athletes competing in different types of sports could be considered a key factor to justify this contradiction [ 62 ].…”
Section: Discussionmentioning
confidence: 99%